1984
DOI: 10.1159/000242009
|View full text |Cite
|
Sign up to set email alerts
|

Iron Status of the Preterm Infant during the First Year of Life

Abstract: The iron status of 49 preterm infants (mean gestational age 33,1 weeks) was assessed serially during the 1st year of life. Haemoglobin concentration, serum ferritin, serum transferrin, serum iron, and transferrin saturation were measured on nine occasions in each infant. In 16 infants of gestational age 28-32 weeks the haemoglobin concentration was significantly lower at 3, 6, and 9 weeks when compared to 33 infants of gestational age 33-36 weeks. For all other measures of iron status there were no significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 21 publications
2
14
0
Order By: Relevance
“…Cord blood ferritin levels in this study are roughly one third of those we have reported previously for preterm babies during the first three days of life 16. Iron levels are about twice as high in cord blood as in samples taken during the first three days of life, and this may be explained by the fact that iron is being transferred to the fetus from the mother through the umbilical vein 16…”
Section: Discussionsupporting
confidence: 59%
“…Cord blood ferritin levels in this study are roughly one third of those we have reported previously for preterm babies during the first three days of life 16. Iron levels are about twice as high in cord blood as in samples taken during the first three days of life, and this may be explained by the fact that iron is being transferred to the fetus from the mother through the umbilical vein 16…”
Section: Discussionsupporting
confidence: 59%
“…Between 25% and 85% of preterm infants develop evidence of iron deficiency during infancy [38]. Unlike full term infants, in whom the condition typically occurs during the second half of infancy, preterm infants are at risk for developing iron deficiency during their first 6 postnatal months [59].…”
Section: Risk Of Iron Deficiency In Preterm Infantsmentioning
confidence: 99%
“…The Hgb nadir is lower and occurs earlier in more premature (gestational age 28–32 wk) infants when compared with those born at a gestational age of 33–36 wk [3]. However, beginning at 9 weeks and continuing until 12 months of age, Hgb concentrations are comparable in the two gestational age groups [3], implying the need for a more robust erythropoiesis and therefore, greater iron requirement in the more prematurely born infants.…”
Section: Risk Of Iron Deficiency In Preterm Infantsmentioning
confidence: 99%
“…Postnatally, copper deficiency [9] or excess iron (released from fetal erythrocytes or derived from nutritional sources) [10,11] may further impair ceruloplasmin's ferroxidase and transferrin's ferric ion binding antioxidant activity and predispose the newborn baby to oxidative Lindeman/Lentjes/van Zoeren-Grobben/ Berger damage. Yet, these possible changes in antioxidant activity have received little attention.…”
Section: Introductionmentioning
confidence: 99%